Pola Radiasi Antena Patch dalam Skala Linier - Annas, Muhamad Azwar; Widodo, Aris; Chasanah, Uswatun; Aisiyah, Muktamar Cholifah; Ningrum, Izza Eka (YASIN, 2022)
An antenna radiation pattern experiment has been carried out with the aim of determining the patch antenna radiation pattern on a logarithmic and linear scale, understanding the properties and principles of the antenna, and understanding the types of antenna radiation patterns. In the experiment, the angle, frequency, and radian intensity data were obtained, and the value of the linear intensity was calculated. With the principle of converting electrical signals into electromagnetic signals. a graph between angle and intensity is obtained. the graph between radian intensity and angle forms a circular pattern, in which the value of intensity and frequency at each point with a difference of 5 degrees has almost the same value. In conclusion, the antenna is a structure that can receive and release electromagnetic waves in the air. The patch antenna used has a unidirectional radiation pattern. Converts electromagnetic signals into electrical signals and vice versa, has a certain radiation pattern, and is easily disturbed by metallic materials.